Party support in the Dail elections 1981-1992: an ecological analysis - Sinnott, Richard; Whelan, Brendan J.; McBride, James (Economic & Social Studies, 1996)
This paper is a contribution to the aggregate-level or ecological analysis of voting behaviour in Ireland. It updates and re-evaluates previous research by considering the six elections of 1981,1982 (February), 1982 (November), 1987, 1989 and 1992. The approach to deriving measures of the independent variables is based on aggregating the Census figures for District Electoral Divisions. The paper begins by critically examining past research in this area focusing especially on the thesis that "agricultural structure" is the main determinant of the Fianna Fail vote. It goes on to present new analyses of party support across each of the six elections for four parties (Fianna Fail, Fine Gael, Labour and Democratic Left/the Workers' Party) using a model incorporating class, urban-rural and liberal-conservative cleavages. The final section attempts to draw some general conclusions about the nature of party support in Ireland and how it has changed over time.
Keywords: Voting behaviour; Elections; Political parties; Ireland; Party support